Procurement Implementation Capability as a Mediator between Integrated Procurement Framework Dimensions and Procurement Outcomes: Evidence from Ghana's Public Sector - O. O. Dwomoh; C. O. Aigbavboa; G. Kaku; M. Addae; F. Asare (AFRICAN JOURNAL OF APPLIED RESEARCH, 2026)
Purpose: This study examines the mediating role of procurement implementation capability in the relationship between integrated procurement framework dimensions and procurement outcomes within the Ghanaian public sector. Design/Methodology/Approach: A quantitative cross-sectional design was employed, drawing on Dynamic Capability Theory and Institutional Theory. Data were collected from 600 procurement professionals and administrators across public institutions in Ghana using structured questionnaires. The hypothesised relationships were tested using Partial Least Squares Structural Equation Modelling (PLS-SEM). Research Limitation: Cronbach's alpha is limited because it is sensitive to the number of items, meaning adding or deleting items can affect its value. Findings: The results reveal that e-procurement adoption significantly enhances both procurement implementation capability and procurement outcomes, while regulatory compliance and transparency factors significantly improve procurement implementation capability but not procurement outcomes directly. Procurement implementation capability partially mediates the relationships between regulatory compliance and procurement outcomes, and between transparency, fairness, accountability and procurement outcomes, but does not mediate the e-procurement–outcomes relationship. Practical Implication: Public procurement entities should prioritise building implementation capabilities, including contract management skills and performance monitoring systems, as regulatory and transparency mechanisms depend substantially on these capabilities to generate performance benefits. Social Implication: Policymakers should address environmental constraints, including inadequate infrastructure, limited technical support, and fragmented supplier databases, to create an enabling environment that accelerates public procurement transformation. Originality/value: This study addresses a significant gap in public procurement by examining both implementation capability and procurement outcomes as endogenous constructs, whereas prior research has traditionally focused on compliance outcomes at the expense of operational performance measures.